Two Puzzling Cases of Headache: A Case Series - Singh, Jasmine; Azad, Chandrika (Journal of Pediatric Neurology, 2023)
Migraine and epilepsy are important causes of morbidity in adolescents and young adults. Mostly the diagnosis is readily made by using the predefined criteria. However, in extremely rare cases, children who present with typical symptoms of migraine with aura or familial hemiplegic migraine might have an underlying etiology of epilepsy. We hereby present the case of two children who presented with migraine-like symptoms but on detailed workup revealed an underlying epilepsy. Both patients responded to antiepileptic medications. These cases highlight the importance of a detailed history and comprehensive investigation plan for such patients to prevent erroneous diagnosis and migraine prophylaxis.
Keywords: headache; migraine; epilepsy; seizures; migralepsy